2022
DOI: 10.1002/aelm.202200171
|View full text |Cite
|
Sign up to set email alerts
|

Tailor‐Made Charged Catechol‐Based Polymeric Ligands to Build Robust Fuel Cells Containing Antioxidative Nanoparticles

Abstract: Cerium oxide nanoparticles (CNPs) are investigated as radical scavengers to increase the durability of polymer electrolyte membrane fuel cells (PEMFCs). However, the practical application of CNPs in PEMFCs is hindered by the low stability of the CNPs during cell operation and the low compatibility of the CNPs with PEM. In this study, as effective antioxidants for PEMs, surface‐engineered CNPs, passivated with dopamine‐based copolymer ligands containing multidentate catechol pendant groups (CNP@DPLs), are repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…S11 in the ESI † ), the AANC surface modification method can be applied to highly uniform and various nanocrystals synthesized in high-boiling point organic solvents for bio and electronic applications. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S11 in the ESI † ), the AANC surface modification method can be applied to highly uniform and various nanocrystals synthesized in high-boiling point organic solvents for bio and electronic applications. 27 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that an amine-assisted catechol-based nanocoating (AACN) provides a molecularly smooth and robust coating layer on metal oxide substrates and nanoparticles. 26,27 In the AACN mechanism, the key roles of separated amine in AACN are enhancement of catechol adhesion, suppression of polymerization derived from catechol, and additional stabilization through an in situ generated catechol-amine adduct. Therefore, the detachment of catecholic ligands from NPs by iron ion catalyzed oxidation of catechol on the surface of Fe 3+ rich iron oxides including 3 nm-sized IONPs can be overcome by the method during the coating process.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we also confirmed the outstanding antioxidation efficacy of CeO x NT by demonstrating the remarkable durability of the Pt/C + CeO x NT cathode. To evaluate PEMFC durability, we subjected the cathodes to a 100-hour OCV-holding durability test, which simulates a harsh acidic environment with the rapid formation of radical species [16,41,42]. and e) were 93 % and 94 %, respectively, significantly higher than those of the pristine Pt/C cathode (74 % and 78 %).…”
Section: Pemfc Performance and Durability Of Catalyst Layersmentioning
confidence: 99%